2021
DOI: 10.1039/d1cc02326h
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of tribenzosilepins from terphenyls and dihydrosilanes by electrophilic double silylation

Abstract: Tribenzosilepins were synthesized from terphenyls and dihydrosilanes using a facile approach using a double sila-Friedel–Crafts reaction. Several silepin derivatives were obtained in moderate to high yield. The reaction system was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In 2021, the research group of Kuninobu reported a double sila‐Friedel‐Crafts reaction of amino‐group‐containing terphenyls 81 and dihydrosilanes 80 using the FLP of B(C 6 F 5 ) 3 and 2,6‐lutidine, affording a series of a seven‐membered heterocyclic tribenzosilepin derivatives 82 in of 24–93 % yield (Scheme 18). [27b] …”
Section: Dual Catalysis Of Boron and Organocatalystmentioning
confidence: 99%
“…In 2021, the research group of Kuninobu reported a double sila‐Friedel‐Crafts reaction of amino‐group‐containing terphenyls 81 and dihydrosilanes 80 using the FLP of B(C 6 F 5 ) 3 and 2,6‐lutidine, affording a series of a seven‐membered heterocyclic tribenzosilepin derivatives 82 in of 24–93 % yield (Scheme 18). [27b] …”
Section: Dual Catalysis Of Boron and Organocatalystmentioning
confidence: 99%
“…Explicitly, the silicon analogues of medicinal molecules exhibit superior pharmacological action . Because of the growing prevalence of the organosilicon skeleton, leading synthetic organic chemists have been spurred to seek out efficient methods to synthesize intricate organosilicon scaffolds . Hydrosilylation of olefins is a very useful method to install a single silyl unit on an olefinic skeleton .…”
Section: Introductionmentioning
confidence: 99%